A randomized, double-blind, placebo-controlled study of flexible doses of levomilnacipran ER (40–120 mg/day) in patients with major depressive disorder - Gommoll, Carl P. (J Drug Assess, 2014)
OBJECTIVE: Levomilnacipran ER is a potent and selective serotonin and norepinephrine reuptake inhibitor (SNRI) approved for the treatment of major depressive disorder (MDD). Efficacy and safety have been evaluated in five Phase II/III studies, four of which met the pre-specified primary efficacy outcome. Results of the negative trial (ClinicalTrials.gov NCT00969150) are reported here. METHODS: A Phase III randomized, double-blind, placebo-controlled trial comparing flexible-dose levomilnacipran ER 40–120 mg/day with placebo was conducted in outpatients with MDD. Patients met the DSM-IV-TR criteria for MDD, had a current episode of depression of at least 4 weeks’ duration, and a Montgomery-Åsberg Depression Rating Scale (MADRS) total score ≥30. The study comprised a 1-week, single-blind, placebo lead-in, 8-week double-blind treatment, and a 2-week down-taper. The primary and secondary efficacy measures were change from baseline to Week 8 in MADRS and Sheehan Disability Scale (SDS) total scores, respectively, analyzed using a mixed-effects model for repeated measures approach. Safety outcomes included adverse events (AEs), laboratory and vital sign measures, the Columbia-Suicide Severity Rating Scale, and the Arizona Sexual Experiences Scale (ASEX). RESULTS: Three hundred and fifty-five patients received the study drug and had ≥1 post-baseline MADRS total score assessment (ITT Population); 81.9% of placebo and 77.1% of levomilnacipran ER patients completed the study. For levomilnacipran ER vs placebo, MADRS (−15.7 vs −14.2) and SDS (−8.8 vs −8.2) total score improvements, and rates of MADRS response (38.5% vs 34.8%) and remission (25.3% vs 23.8%) were numerically greater but differences were not statistically significant. Levomilnacipran ER was generally well tolerated. More levomilnacipran ER patients vs placebo reported AEs; the most common AEs for levomilnacipran ER were nausea (17%) and headache (16%). Mean changes in most safety measures were small and similar between groups. There were no meaningful differences in total ASEX scores between groups. LIMITATIONS: Short duration of treatment, inclusion and exclusion criteria, and lack of an active comparator. CONCLUSION: Numerical improvements for levomilnacipran ER vs placebo were detected in this study, but the differences were not statistically significant; levomilnacipran ER was generally well tolerated.